Know Thy Model: Charting Molecular Homology in Stromal Reprogramming Between Canine and Human Mammary Tumors - Markkanen, Enni (Frontiers in Cell and Developmental Biology, 2019)
Spontaneous canine simple mammary tumours (CMTs) are often viewed as models of human breast cancer. Cancer-associated stroma (CAS) is central for initiation and progression of human cancer, and is likely to play a key role in canine tumours as well. Until recently, however, canine CAS in general, and in CMT in particular, lacked detailed characterisation and it remained unclear how canine and human CAS compare. This void in knowledge regarding canine CAS and the resulting lack of unbiased cross-species analysis of molecular homologies and differences undermined the validity of the canine model for human disease. To assess stromal reprogramming in canine breast tumours, we have recently established a protocol to specifically isolate and analyse CAS and matched normal stroma from archival, formalin-fixed paraffin embedded (FFPE) clinical tumour samples using laser-capture microdissection followed by next-generation RNA-sequencing. Using this approach, we have analysed stromal reprogramming in both malignant canine mammary carcinomas as well as benign canine mammary adenomas in a series of studies. Our results demonstrate strong stromal reprogramming in CMTs and identify high-grade molecular homology between human and canine CAS. Here, I aim to give a short background on the value of comparative oncology in general, and spontaneous CMT in particular. This will be followed by a concise review of the current knowledge of stromal reprogramming in both malignant canine mammary carcinoma and benign adenoma. Finally, I will conclude with insights on highly conserved aspects of stromal reprogramming between CMT and human breast cancer that accentuate the relevance of CAS in CMT as a model for the human disease.